2021
DOI: 10.3390/microorganisms9020392
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community Structure Driven by a Volcanic Gradient in Glaciers of the Antarctic Archipelago South Shetland

Abstract: It has been demonstrated that the englacial ecosystem in volcanic environments is inhabited by active bacteria. To know whether this result could be extrapolated to other Antarctic glaciers and to study the populations of microeukaryotes in addition to those of bacteria, a study was performed using ice samples from eight glaciers in the South Shetland archipelago. The identification of microbial communities of bacteria and microeukaryotes using 16S rRNA and 18S rRNA high throughput sequencing showed a great di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
(59 reference statements)
1
8
0
Order By: Relevance
“…Other classes such as Thermodesulfobacteria, Chrysiogenetes, and Thermoprotei were scarcely represented (Figure 2A). These proportions of bacteria are analogous to those found in glaciers located in similar latitudes such as some Alpine (Franzetti et al, 2017;Azzoni et al, 2018), or Asian glaciers (Chen et al, 2016), but different from those found in the polar glaciers (García-Lopez et al, 2021). Some groups were exclusively identified in the oldest samples as the bacterial phyla Fusobacteria and Calditrichaeota.…”
Section: Microbial Community Compositionsupporting
confidence: 62%
See 1 more Smart Citation
“…Other classes such as Thermodesulfobacteria, Chrysiogenetes, and Thermoprotei were scarcely represented (Figure 2A). These proportions of bacteria are analogous to those found in glaciers located in similar latitudes such as some Alpine (Franzetti et al, 2017;Azzoni et al, 2018), or Asian glaciers (Chen et al, 2016), but different from those found in the polar glaciers (García-Lopez et al, 2021). Some groups were exclusively identified in the oldest samples as the bacterial phyla Fusobacteria and Calditrichaeota.…”
Section: Microbial Community Compositionsupporting
confidence: 62%
“…In these reports, the majority of OTUs belonged to Chlorophyta and Fungi. However, in polar glaciers, the eukaryotic proportions were more diverse and influenced by a range of local factors, so they are not comparable to those of the Pyrenean glaciers (Anesio et al, 2017;García-Lopez et al, 2021).…”
Section: Microbial Community Compositionmentioning
confidence: 95%
“…Bacteria inside glaciers are represented by the phyla Proteobacteria (mainly Gammaproteobacteria and Alphaproteobacteria), Bacteroidetes (class Bacteroidia, order Flavobacteriales), Firmicutes, Actinobacteria, Acidobacteria, Verrucomicrobia, Planctomyetes, and Gemmatimonadetes with prevalent genera Flavobacterium, Luteolibacter, Rhodoferax, Rhodanobacter, Dokdonella, and Polaromonas [52,135]. Typical Antarctic psychrotrophic and psychrotolerant bacteria in glaciers include the genera Polaribacter, Polaromonas, Psychrobacter, Psychromonas, and Cryobacterium.…”
Section: Ice and Glacial Microbial Communitiesmentioning
confidence: 99%
“…The concentration of major (Cl, S, C, K, Na, P, Xe, Mg, Ca, Fe, Co, Mn, Ti, Cr, and Ni), minor, and trace elements ( Supplementary Table S1 ) was quantified by inductively coupled plasma-mass spectrometry (ICP-MS) on a PerkinElmer ELAN9000 ICP-MS quadrupole spectrometer. The samples were introduced into the ICP-MS via a RytonTM cross-flow nebulizer (PerkinElmer, Waltham, MA, United States), Scott spray chamber (PerkinElmer), and Cetac ASX-510 autosampler (Omaha, Nebraska, United States; García-Lopez et al, 2021a ).…”
Section: Methodsmentioning
confidence: 99%